Measurements of the charm jet cross section and nuclear modification factor in pPb collisions at sNN=5.02 TeV - Sirunyan, A. M.; Tumasyan, A. R.; Adam, Wolfgang; Asilar, Ece; Bergauer, Thomas; Md. Ali, Mohd. Adli (Elsevier BV, 2017)
The CMS Collaboration presents the first measurement of the differential cross section of jets from charm quarks produced in proton–lead (pPb) collisions at a nucleon–nucleon center-of-mass energy of √sNN = 5.02 TeV, as well as results from charm quark jets in proton–proton (pp) collisions at √s = 2.76 and 5.02 TeV. By comparing the yields of the pPb and pp collision systems at the same energy, a nuclear modification factor for charm jets from 55 to 400 GeV/c in pPb collisions at √sNN = 5.02 TeV of RpA = 0.92 ± 0.07 (stat)± 0.11 (syst) is obtained. This is consistent with an absence of final-state energy loss for charm quarks in pPb collisions. In addition, the fraction of jets coming from charm quarks is found to be consistent with that predicted by pythia 6 for pp collisions at √s = 2.76 and 5.02 TeV, and is independent of the jet transverse momentum from 55 to 400 GeV/c.